Creating culture through media and communication - Moreira, Sonia Virginia; Moles, Katia; Robinson, Laura; Schulz, Jeremy (Studies in media and communications, 2024)
Sponsored by the Brazil-U.S.Colloquium on Communication Studies of the Brazilian Society for Interdisciplinary Studies in Communication and the Communication, Information Technologies, and Media Sociology Section of the American Sociological Association (CITAMS), this volume of Emerald Studies in Media and Communications is entitled Creating Culture Through Media and Communication. The volume is a vibrant collaboration of global voices addressing the media and communications challenges of our time. Contributors ask us to reconsider the ethical implications of media and technology from historical, contemporary, and future perspectives. In addition, case studies show the diverse ways that cultural media production has ripple effects throughout larger society. Authors ask important questions about how digitalization is shaping our everyday lives, as well as how the ethics of tech is needed now more than ever with the sea change occasioned by AI.